The Results of the Technical-Technological Study of Ceramics from the Late Eneolithic Campsite of Bolshaya Rakovka II - Irina N. Vasilyeva; Arkady I. Korolev (Археология евразийских степей)
The article analyzes the ceramics of the Late Eneolithic campsite of Bolshaya Rakovka II (Samara region). It is characterized by the complete predominance of straight-walled vessel forms with rounded bottoms. The ornamentation primarily features impressions from comb-shaped stamps, alongside pit and cord impressions. Based on morphological analysis, such pottery were attributed to the Chekalino type of the Sok River basin. The characteristics of ceramics are similar to the materials of the Late Eneolithic in the adjacent areas: from the Lower Volga region to the forest zone of the Middle Volga and the Lower Kama region. The closest parallels for this pottery are found in the Tok materials (Samara River basin). The site is of great importance for the study of issues of cultural affiliation, origin, chronology and periodization of the Late Eneolithic of the Middle Volga region. To develop these issues, a study of the ceramics of the campsite was undertaken using a technical-technological analysis according to the method by A.A. Bobrinsky. This study identified widespread traditions of utilizing silty clays as raw material, crushed shell additives, and organic temper in the molding paste. It revealed that the Chekalino type ceramics are not homogeneous. The greatest variability was observed in the group of ceramics decorated with comb-shaped stamps.